Protein enrichment of coconut (Cocos Nucifera L.) residue by Fusant 88 - Banno, Jossette Mercado; De Leon, Sonia Y. (1993)
Optimization of the following ferementation parameters: pH level, fermentation time and spore load of the inoculum was studied for the protein enrichment of coconut residue by F88. The first phase involved the determination time and pH level. A marked increase in protein content of coconut residue without development of dark pigmentation was achieved after a day of fermentation of the substrate which pH was not adjusted. The second phase involved the determination of the optimum spore load of the inoculum. A spore load of 10^3 cells/mL was found sufficient to effect significant protein enrichment. The last phase involved the evaluation of the developed process. With the optimized parameters obtained in Phases I and II, the % crude protein content of the microbial biomass produced is approximately 25% while its protein yield is about 15%. The enriched coconut residue was white comparable to the white-colored control, with moisture content of 2% and a yield of 60.3%.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut; Enriched foods